Bacterial cellulose membrane as flexible substrate for organic light emitting devices - Legnani, C.; Vilani, C.; Calil, V. L.; Barud, H. S. [UNESP]; Quirino, W. G.; Achete, C. A.; Ribeiro, Sidney José Lima [UNESP]; Cremona, M. (Elsevier B.V. Sa, 2008)
Bacterial cellulose (BC) membranes produced by gram-negative, acetic acid bacteria (Gluconacetobacter xylinus), were used as flexible substrates for the fabrication of Organic Light Emitting Diodes (OLED). In order to achieve the necessary conductive properties indium tin oxide (ITO) thin films were deposited onto the membrane at room temperature using radio frequency (r.f) magnetron sputtering with an r.f. power of 30 W, at pressure of 8 mPa in Ar atmosphere without any subsequent thermal treatment. Visible light transmittance of about 40% was observed. Resistivity, mobility and carrier concentration of deposited ITO films were 4.90 x 10(-4) Ohm cm, 8.08 cm(2)/V-s and -1.5 x 10(21) cm(-3), respectively, comparable with commercial ITO substrates. In order to demonstrate the feasibility of devices based on BC membranes three OLEDs with different substrates were produced: a reference one with commercial ITO on glass, a second one with a SiO(2) thin film interlayer between the BC membrane and the ITO layer and a third one just with ITO deposited directly on the BC membrane. The observed OLED luminance ratio was: 1; 0.5; 0.25 respectively, with 2400 cd/m(2) as the value for the reference OLED. These preliminary results show clearly that the functionalized biopolymer, biodegradable, biocompatible bacterial cellulose membranes can be successfully used as substrate in flexible organic optoelectronic devices. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: OLED; Transparent conducting oxides; Solid state lightning; Flexible organic electronics ''> onducting oxides; Solid state lightning; Flexible organic electronics